Shadow Banking, Bank Liquidity and Monetary Policy Shocks in Emerging Countries: A Panel VAR Approach - zhou, sheunesu (Journal of Economics and Behavioral Studies, 2020)
The study provides an analysis of the relationships between monetary policy, shadow banking and bank liquidity in emerging market economies. It is aimed at broadening knowledge on the effect of shadow banking on monetary policy transmission. Furthermore, the study seeks to analyze the impact of changes in bank liquidity on the growth of the shadow banking sector. We employ panel VAR technique to analyse the dynamics of monetary policy, shadow banking and bank liquidity using data for 15 emerging economy countries. A contractionary monetary policy shock results in a decrease in shadow banking and a decrease in bank liquidity. We also find that a positive shock in bank liquidity increases shadow bank growth and a positive shock in shadow banking also increases bank liquidity. The results point to complementarity between shadow banking and bank liquidity; and the interconnectedness between the two markets in emerging economies. We suggest continuous monitoring of shadow banking activities to minimize transmission of risk from the shadow banking system into the banking sector.